Linear Quadratic Regulator Control of Rotary Inverted Pendulum Using Elvis III Embedded Platform - Ming-Hung Lin; Jun-Qi Huang; Yao-Hung Tsai; Chun-Chieh Chang; Cheng-Yi Chen (Engineering Proceedings, 2025)
Modern education is characterized by diversity and the need for extensibility. Educational experimental platforms are rapidly evolving according to these factors. However, software and hardware are provided by major domestic manufacturers, which imposes limitations on the development of teaching materials. We investigate the implementation of a rotational inverted pendulum control system within the NI ELVIS III embedded system. The mathematical model of the rotational inverted pendulum is constructed using Lagrangian equations and then represented in matrix form. Following linearization of the nonlinear state equations, the linear quadratic regulator (LQR) controller of the rotational inverted pendulum apparatus is designed and implemented on the NI ELVIS III embedded system by using LabVIEW graphical programming software. Illustrations are generated to compare the continuous tracking performance of LQR and PID controllers with preset target values. The results are then analyzed to evaluate and contrast the effectiveness of both control strategies in tracking the target values. The findings of this study enhance the development of educational content related to the ELVIS III embedded system’s experimental platform.